STRATEGI KOMUNIKASI MELALUI 4P COFFEE SHOP “WARUNG MERAPI 13” DENGAN FOOD TRUCK DALAM MENARIK MINAT PEMBELI - Alif Puji Utomo; Sihabuddin Sihabuddin (Solidaritas, 2025)
The increasing coffee consumption in Indonesia has encouraged the rapid growth of coffee shopswith various concepts, including mobility-based innovations such as food trucks. However, theintense competition within the coffee industry requires business owners not only to rely on productquality but also to apply effective marketing communication strategies. Warung Merapi 13, a food-truck-based coffee shop in Grobogan Regency, faces challenges in attracting consumer interest insemi-urban areas due to limited promotion and the tight competition within the culinary business.This study examines the communication strategy of Warung Merapi 13 Coffee Shop through theuse of food trucks in attracting buyers in Grobogan, Central Java. The research focuses on theapplication of the marketing mix (4P) as a communication strategy through food truck media insemi-urban areas. A descriptive qualitative approach with a case study method was employed. Datawere collected through participatory observation, in-depth interviews, as well as social mediadocumentation and food truck visual branding. Data analysis was conducted using the interactivemodel of Miles, Huberman, and Saldana, supported by triangulation to ensure the validity offindings. The results show that Warung Merapi 13 consistently applies all four elements of themarketing mix (4P) in its communication strategy to attract consumers. The product strategyhighlights the uniqueness of the coffee menu and service experience through food trucks, while thepricing strategy is set competitively based on the purchasing power of the local community.Placement is implemented through mobile food trucks operating in strategic locations to reachdiverse consumers. Promotional strategies utilize social media, attractive visual branding, anddirect interaction with customers. The integration of these 4P strategies received positive responsesfrom consumers in the form of increased brand awareness, loyalty, and purchase intention. The useof food trucks as an experience-based marketing medium has been proven to strengthen WarungMerapi 13 communication strategy. It is recommended that Warung Merapi 13 continue to enhancethe consistency of digital promotion, build collaborations with local communities, and present localstorytelling-based content innovations to further increase customer attraction and loyalty.